Evaluation Media Design Of Maharah Kitabah Learning Through "Sekolahku" Web At Al Hikmah Boarding School High School Batu - Abdul Muhith,; Harits Ibadurrahman,; Nur Hasaniyah, (Shaut al Arabiyyah, 2025)
The absence of students during the evaluation period is due to various factors and reasons such as going to Umrah worship with family, returning home due to illness (skorsing), suspension due to violations, etc. while students must still get learning facilities even though they are not in the school environment. This study aims to determine the Web used as a medium for evaluating maharah kitabah learning at Al Hikmah Boarding School High School Batu. The approach used in this study is a qualitative approach with the Miles and Huberman model, and the data collection techniques used are observation, interviews, and documentation. For data validity, researchers use the data source triangulation method. The results showed that the Web used as a medium for evaluating maharah kitabah learning at Al Hikmah Boarding School High School Batu was the "Sekolahku" web as a solution to solve the problem of student absenteeism during the learning evaluation.